Analysis of clinico-etiological pattern of adverse cutaneous drug reactions - Warda Orf Rida Naeem; Hira Tariq; Saelah Batool; Shahbaz Aman (Journal of Pakistan Association of Dermatologists, 2023)
Objective To determine the frequency of various adverse cutaneous drug reactions and drugs causing these reactions in patients presenting to a tertiary care hospital. Methods This cross-sectional survey was carried out at Dermatology Department of Services Hospital, Lahore for six months. Patients who fulfilled the inclusion criteria were enrolled. Adverse drug reactions were assessed for causality, using Naranjo Algorithm. Patients were evaluated clinically for the type of drug reaction. Patients were asked for drugs/medicine used before appearance of adverse cutaneous drug reactions. Data was stratified for age, gender and duration of symptoms to address the role of effect modifiers. Post-stratification, chi-square test was applied to compare types of adverse drug reaction and medicines involved. Results Among 150 patients, 71 (47.3%) were males and 79 (52.7%) were females. Age range in this study was from 10 to 70 years with mean age of 44.3Â±8.7 years. According to type of adverse drug reaction, 37 (24.7%) patients had maculopapular rash, 23 (15.3%) had urticarial drug reaction, 20 (13.3%) had acneiform eruption, 19 (12.7%) had fixed drug eruption, 13 (8.7%) had Erythroderma, 11 (7.3%) had DRESS, 9 (6.0%) had Stevens-Johnson syndrome, 8 (5.3%) had erythema multiforme, 7 (4.7%) had toxic epidermal necrolysis and 3 (2.0%) had drug-induced hyperpigmentation. Phenytoin and diclofenac were the commonest offending drugs. Conclusion Knowledge of pattern and causative drugs of adverse cutaneous drug reactions is of utmost importance for any clinician as their consequences can be life threatening as well. Key words Cutaneous Adverse Drug Reactions, Drug, DRESS.